Edukasi Hybrid Entrepreneurship Pada Mahasiswa Politeknik Negeri Madiun Untuk Meningkatkan Wawasan Kewirausahaan - Hifzhan Frima Thousani; Ridho Muarief; Priyanto (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Urged by the fulfillment of increasing needs, some people who become employees and receive salaries for a certain period decide to have an additional job. Some people decided to manage a business as an effort to get more additional income. Besides, when college student graduation, they tend become job seekers linear to their study rather than become job creators. Manage business as well as being an employee should be a solution but holding more than one job, requires strategic plan to be able to hold full responsibilities. The reason student are chosen is to be able to grow and develop interest as entrepreneurs in creating jobs. So an educational webinar on hybrid entrepreneurship was held, namely managing a business while carrying out the main job as an employee of the company. The method used to deliver this issues is lectures with participants of the webinar is Madiun State Polytechnic students. The prospect result of this webinar is that students are able to have knowledge about hybrid entrepreneurship to be used in decision making.